Szkoły typu Open-Air: eksperymenty architektoniczno-pedagogiczne szkolnictwa w pierwszych dziesięcioleciach XX wieku - Cezary Szpytma (Problemy Wczesnej Edukacji)
The aim of the article is to present the contribution of Open-Air schools in the context of the evolution of the school environment and development of modern pedagogy. The article takes into account the historical context of evolution and the historical development of pedagogical ideas. The article focuses on the connection between pedagogy and architecture – regarding school, both disciplines are inextricably linked. Pedagogy is the theoretical foundation of teaching practice, implemented in an architectural space. The quality of this space is of great importance for learning outcomes. Consciously the design and architecture of a school creates something more than a simple housing for the process of education. It can create an environment for education and could strengthen that process in a synergistic manner. In reality, we can observe almost the opposite situation, when the school space, instead of comprehensively stimulating the students, becomes a materialized symbol of the oppressive nature of the educational system. Open-Air schools of the early twentieth century seem to be still an avant-garde and a model, which should be rediscovered. They offer the opportunity to develop social, emotional, and creative skills. These objectives are itemized by many as essential for education in the future.